Investigation of the Role of Sr and Development of Superior Sr-Doped Hexagonal BaCoO3-δPerovskite Bifunctional OER/ORR Catalysts in Alkaline Media - Mondal R.; Ratnawat H.; Mukherjee S.; Gupta A.; Singh P. (My University, 2025)
Superior electrocatalytic activity of catalysts for oxygen evolution reaction (OER) and oxygen reduction reaction (ORR) enhances the reversible energy storage efficiency of metal-air batteries and electrochemical water splitting performances to produce hydrogen. Sr incorporation in the BaCoO3-δlattice in the form of 2H-type Ba1-xSrxCoO3-δ(0 ≤ x ≤ 0.5) perovskites enhances both ORR and OER activities. A relatively low overpotential of 395 mV at 10 mA/cm2, lower Tafel slope of 64.95 mV dec-1, and good stability up to 500 cycles (10% reduction of current density and overpotential shift to a 0.04 V higher value) in a 0.1 M KOH electrolyte were obtained for the Ba0.5Sr0.5CoO3-δelectrode. Incorporation of Sr in the BaCoO3-δlattice decreases the Co-O-Co bond angle that results in a superior orbital overlap between Co(3d) and O(2p) orbitals and a decrease in lattice parameters that generates lower surface oxygen separation pathways and a large number of active sites on the (011) planes, making Ba0.5Sr0.5CoO3-δa superior catalyst with increased OER/ORR activity. The formation of oxygen-vacant CoO5octahedra containing surface oxygen vacancies, the presence of Co3+/4+valence states, and the superior overlap between O(2p)-Co(3d) bands (covalency increases) result in a higher electronic conductivity, a lower flat band potential, and improved OER and ORR activities. The key highlight of this work is the matching of the onset potential with the calculated flat band (Efb) potential from the Mott-Schottky plot. The Mott-Schottky plot was utilized to calculate the flat band potential (Efb) that indicates the basic information about the electrochemical interface potential between the electrode and the electrolyte, and in the case of Ba0.5Sr0.5CoO3-δ, it matches very well with the onset potential for the OER activity of the catalyst. © 2022 American Chemical Society. All rights reserved.